USAHATANI YANG BERKEADILAN GENDER DAN MENGUNTUNGKAN - Elsje Pauline Manginsela (Sam Ratulangi University, 2017)
This article aims to promote the use of formulas that can provide information on whether a farm not only profitable but also have gender equality. This paper describes the formula and how to apply them, which is based on a review of secondary data collected from various literatures. Issues highlighted in this paper is the measuring instrument to assess whether a farm run by farmers profitable and gender so that it can farm resilience, developing and sustainable? Based on the application of the formula on a farm that is exemplified in this paper it will be concluded whether a farm has a chance to survive in the face of crisis, growing and sustainable.